Liquidity and stock returns in order driven markets : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Finance at Massey University - Marshall, Ben (Massey University, 1999)
This thesis examines the relationship between liquidity and stock returns in the New Zealand and Australian stock markets, for the periods of 1993 to 1998 and 1994 to 1998 respectively. There is evidence to suggest that investors are compensated for holding less liquid stocks with higher returns. However, this is the first study (that the author is aware of) to test the return-liquidity relationship in pure order driven stock exchanges. The combined use of bid-ask spread, turnover rate, and amortised spread as proxies for liquidity, also makes this study unique. Previous studies have investigated the return-liquidity relationship using only one or two of these proxies. In addition to liquidity, other factors that have been found by previous researchers to influence stock returns, such as beta, size, and book-to-market equity are also considered. Seemingly Unrelated Regressions (SUR) and a variant of the General Pooled Cross-Sectional Time-Series Model, known as the Cross Sectionally Correlated Timewise Autoregressive (CSCTA) Model, form the methodological basis for this research. A small liquidity premium is found in both markets. This premium persists for the entire year in the Australian market, while in the New Zealand market the premium is only evident in the month of January. There is strong evidence of a negative size effect in Australia. In New Zealand, there is weak evidence of a negative size effect in the month of January. The returns of high book-to-market equity (value) firms are found to be larger than those of their low book-to- market equity (growth) firm counterparts in New Zealand.
Keywords: Liquidity (Economics); Share prices; Stock returns, New Zealand; Stock returns, Australia